Modelos estocásticos para disseminação de informação - Silva, Daniel Antônio Mendonça da (2013)
This work has the main objective to study a of the propagation of information sets N e Z:We consider three models of spreading information. The first model takes into account the power of each individual in transmitting information. The second model takes into account the power of every individual to receive information. In the third model this power is given by the amount of life and the probability that individuals have to jump right.